2019
DOI: 10.1016/j.neuroimage.2018.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Automated processing pipeline for neonatal diffusion MRI in the developing Human Connectome Project

Abstract: The developing Human Connectome Project is set to create and make available to the scientific community a 4-dimensional map of functional and structural cerebral connectivity from 20 to 44 weeks post-menstrual age, to allow exploration of the genetic and environmental influences on brain development, and the relation between connectivity and neurocognitive function. A large set of multi-modal MRI data from fetuses and newborn infants is currently being acquired, along with genetic, clinical and developmental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 82 publications
4
160
0
Order By: Relevance
“…In both the nociception-paradigm and dHCP datasets, infants with larger noxious-response amplitudes (or for the dHCP data, larger predicted values) had smaller MD and larger FA values throughout the brain (Supplementary Figure 7). White matter MD decreases and FA increases throughout development into adulthood 26 , and similar to the functional measures, these developmental trends are discernible within the perinatal period 27 . The combination of negative MD and positive FA correlations suggest specific structural maturational influences, such as increasing white matter myelination, or fibre packing density, or both.…”
Section: Discussionsupporting
confidence: 53%
“…In both the nociception-paradigm and dHCP datasets, infants with larger noxious-response amplitudes (or for the dHCP data, larger predicted values) had smaller MD and larger FA values throughout the brain (Supplementary Figure 7). White matter MD decreases and FA increases throughout development into adulthood 26 , and similar to the functional measures, these developmental trends are discernible within the perinatal period 27 . The combination of negative MD and positive FA correlations suggest specific structural maturational influences, such as increasing white matter myelination, or fibre packing density, or both.…”
Section: Discussionsupporting
confidence: 53%
“…Standard neuroimaging techniques do not provide quantifiable data on brain microstructural architecture, however this study has demonstrated a reproducible and reliable method for obtaining whole brain maps with quantifiable estimates of brain microstructure. This measure is stable enough to be used in longitudinal studies lasting at least up to three months; and provides information on a voxel-or region-wise basis for analysis of subcortical structures, lesions, or developing brains (Dhollander et al, 2017;Mito et al, 2018;Mito et al, 2019;Bastiani et al, 2019). Related microstructural analysis of free water signal fractions has been performed in the context of Parkinson's disease (Ofori et al, 2015;Burciu et al, 2016), Schizophrenia (Pasternak et al, 2012;Mandl et al, 2015), and concussion (Pasternak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by utilizing the FSL package ( "topup" and "eddy" ) to correct for susceptibility induced (EPI) distortions, eddy currents, and subject motion (Smith et al, 2004;Andersson et al, 2003;. Finally, we upsampled the preprocessed data to 1.3⨉1.3⨉1.3mm 3 isotropic voxels (Greenspan, 2008;Kuklisova-Murgasova et al, 2012;Bastiani et al, 2019). These preprocessing steps are largely similar to those used in other recently published works (Bastiani et al, 2019;Pietsch et al, 2019;Mito et al, 2019;Aerts et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 40 subjects from the developing HCP project (Hughes et al, 2017;Bastiani et al, 2019). The data was acquired using TR=3800 ms and TE=90 ms.…”
Section: Real Datamentioning
confidence: 99%